Pelvic ectopic kidney with malrotation: a rare case report of renal cell carcinoma - Aregala, Praneeth; Gowda, Sreehari; Marda, Sachin; Jyoshna, T. M. (International Surgery Journal, 2025)
The incidence of renal cell carcinoma in a pelvic kidney is rare and has only been reported in a very small number of cases. We report a 42 years old female patient presented with haematuria. CT scan showed large heterogeneous soft tissue mass arising from a right interpolar region of pelvic kidney with saccular aneurysm and peripheral hpoenhancing lesion. Histopathology after radical nephroureterectomy showed grade II clear-cell renal carcinoma. Renal cell carcinoma of ectopic kidney is a rare disease. Even though the presentation might be atypical and challenging, the treatment strategy is still the same as for tumours of orthotopic kidneys.